Digital transformation of the economy at the regional level: strategy and specifics - N. T. Avramchikova; A. O. Rukosuev (E-Management)
The article defines the concepts of strategic planning, digitalisation, digital transformation in relation to public administration. The specifics of digital transformation in this field at the regional level are analyzed and an assessment of the effectiveness of the implementation of its components is made. The authors note that the direct use of foreign models of strategic planning in the field of digital transformation is problematic in Russian practice, since they do not consider the specifics of the Russian economy associated with the weak economic development of territories. It is concluded in the text that it is necessary to create a system of state strategic planning that takes into account these features. Disadvantages of strategic planning of digital transformation are investigated, mechanisms of research of typical errors are studied. The basis of this research was the analysis of strategic attitudes in the field of digital transformation of business processes and social interactions of the Krasnoyarsk Krai of the Russian Federation. A critical assessment and completeness of the methodological provisions of the federal project Digital Public Administration is carried out, the positive and negative aspects of this document are investigated. The article assesses its impact on the digital transformation in public administration in the Krasnoyarsk Krai. The authors reveal the inconsistency of goal-setting with the idea of digital transformation, the lack of alignment of relations between stakeholders, the low methodological study of the issue and the insufficient assessment of regional specifics. It is concluded that at present the digital economy development strategy is not fully provided with the necessary amount of funding and does not reflect the needs of strategic planning of digital transformation in the public administration system.